Jeremy Bentham: como medir os prazeres e as dores cálculo da felicidade - Otaviani, Márcia Cristina (2008)
Jeremy Bentham (1748-1832) was na English philosopher who wrote about how human actions should be treated. He believed only two sovereign masters should govern us all. Pleasure and pain should tell us what is right and what is wrong. Bentham thought that every man seeks actions to maximize pleasure and diminish pain. The author believed that human actions could be treated in a scientific fashion. To his objective, he proposed a moral science and, as a criteria to measure the masters which manage human actions Bentham developed a theory to quantify pleasure and pain. Such calculus will be presented in this paper in a manner to verify its characteristics. Hereby, we will demonstrate how science and art were understood by the author, as well as, his thoughts regarding logic, language and how knowledge has been perceived by man